TEACHERS PERCEPTION TOWARDS SOCIAL MEDIA BASED LEARNING - SANDEEP BHATT, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In the era of information and communication technology (ICT), both developed and developing nations are putting a lot of emphasis on social-based learning (SMBL). Social media relies on a variety of platforms, including YouTube, Google, Facebook, Twitter, Instagram, and Whatsapp. People use these platforms for a variety of learning and communication purposes. Younger generations are particularly interested in social media-based education, both in formal and informal settings. It makes it easier for them to interact, take part, and learn cooperatively. For professional development, teachers and students regularly employ a variety of e-format educational studies that are available. According to the study, a significant proportion of students and researchers in India regularly utilize social media for both learning and research purposes. The function of social media in teaching and learning has received very little attention in studies to far. Using varied perspectives on student teachers in the context of their course background, the present article aims to explore the many levels of uses by teacher education at the B.Ed. and M.Ed. levels.